A comparison of capsazepine and ruthenium red as capsaicin antagonists in the rat isolated urinary bladder and vas deferens. - Maggi, C. A. (1993)
1. The ability of capsazepine, a recently developed capsaicin receptor antagonist, to prevent the effects of capsaicin on the rat isolated urinary bladder (contraction) and vas deferens (inhibition of electrically-evoked twitches) was compared to that of ruthenium red, a dye which behaves as a functional antagonist of capsaicin. 2. In the rat bladder, capsazepine (3-30 microM) produced a concentration-dependent rightward shift of the curve to capsaicin without any significant depression of the maximal response to the agonist. By contrast, ruthenium red (10-30 microM) produced a non-competitive type of antagonism, characterized by marked depression of the maximal response attainable. Similar findings were obtained in the rat isolated vas deferens in which capsazepine (10 microM) produced a rightward shift of the curve to capsaicin while ruthenium red (3 microM) depressed the maximal response to the agonist. 3. At the concentrations used to block the effect of capsaicin, neither capsazepine nor ruthenium red affected the contractile response of the rat urinary bladder produced by either neurokinin A or electrical field stimulation or the twitch inhibition produced by rat alpha-calcitonin gene-related peptide (alpha CGRP) in the vas deferens. 4. These findings provide additional evidence that both capsazepine and ruthenium red are valuable tools for exploration of the function of capsaicin-sensitive primary afferent neurones. The antagonism of the action of capsaicin by capsazepine is entirely consistent with the proposed interaction of this substance with a vanilloid receptor located on primary afferents, while the action of ruthenium red apparently involves a more complex, non-competitive antagonism.